Functional Digital Nudges: Identifying Optimal Timing for Effective Behavior Change - Purohit, Aditya Kumar; Holzer, Adrian (My University, 2019)
Digital nudges hold enormous potential to change behavior. Despite the appeal to consider timing as a critical factor responsible for the success of digital nudges, a comprehensive organizing framework to guide the design of digital nudges considering nudge moment is yet to be provided. In this paper, we advance the theoretical model to design digital nudges by incorporating three key components: (1) Identifying the optimal digital nudge moment (2) Inferring this optimal moment and (3) Delivering the digital nudge at that moment. We further discuss the existing work and open research avenues.
, 2019
Keywords: Timing; Digital Nudge; Behavioral change interventions; Nudge moment